OER Action Plan for Kansas State University’s Open Alternative Textbook Initiative - Finch, Emily G. (My University, 2021)
This report submitted in completion of the Open Educational Network's OER Librarian Certification program examines the K-State Open Alternative Textbook Initiative (OATI) and its needs past, present, and future. It creates a list of goals and proposes new metrics for that will help bring the project into its 10th year (2023) with success, community, and sustainability in mind. The report is written from the perspective of the Scholarly Communication and Copyright Librarian who has met the administrative needs of the project since February of 2020. This report serves as a checklist and proposal moving forward but also as a resource to other OER librarians/enthusiasts interested in the administration and future of the OATI. The introduction provides an overview on how K-State administers its program, followed by sections that lay out needs and possible solutions for moving forward with the project, and it ends with an appendix that provides an overview of OATI reporting and administration. The documents in the appendices are licensed from the Open Alternative Textbook Initiative for others to reuse in their OER efforts.
Keywords: Open educational resources; Open Educational Network; Open Alternative Textbook Initiative